2007
DOI: 10.1038/sj.mt.6300090
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing AAV Capsid-specific CD8+ T Cells are Unable to Eliminate AAV-transduced Hepatocytes

Abstract: The goal of these studies was to test whether adeno-associated virus (AAV) capsid-specific CD8(+) T cells cause loss of hepatic AAV-mediated gene expression in experimental animals. Mice immunized with adenoviral vectors expressing AAV capsid or with AAV vectors developed CD8(+) T cells in blood, lymphatic tissues, and liver to epitopes shared between AAV2 and AAV8, and serotype-specific neutralizing antibodies. At the height of the T cells' effector phase, mice were infused with a heterologous AAV vector expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 26 publications
0
89
3
Order By: Relevance
“…50 Several studies demonstrated that AAV capsid-specific CTLs also do not appear to play a role in elimination of AAVtransduced cells in mouse models. 85,86 The fact that capsid-specific T cells in animal models were unable to lyse AAV-transduced hepatocytes sparked a scientific debate about alternative explanations other than capsid cross-presentation. One interesting consideration was that latent AAV genomes, which occur endogenously with high abundance in humans, might have become activated by homologous recombination with vector genomes-leading to the expression of capsid proteins.…”
Section: T-cell Responses To the Aav Capsid: A New Challengementioning
confidence: 99%
“…50 Several studies demonstrated that AAV capsid-specific CTLs also do not appear to play a role in elimination of AAVtransduced cells in mouse models. 85,86 The fact that capsid-specific T cells in animal models were unable to lyse AAV-transduced hepatocytes sparked a scientific debate about alternative explanations other than capsid cross-presentation. One interesting consideration was that latent AAV genomes, which occur endogenously with high abundance in humans, might have become activated by homologous recombination with vector genomes-leading to the expression of capsid proteins.…”
Section: T-cell Responses To the Aav Capsid: A New Challengementioning
confidence: 99%
“…RBCs were lysed with ACK lysis buffer (Life Technologies, Grand Island, NY) treatment for 1-5 min. Lymphocytes were isolated from spleen and liver as described previously (39). Lymphocytes were isolated from lungs as follows.…”
Section: Isolation Of Lymphocytesmentioning
confidence: 99%
“…Splenocytes were in addition stained with a live cell dye, Abs to CD8 and CD44 and the NP-tet to determine percentages of NP-responsive CD8 + T cells. Percent-specific lysis was calculated as described (39).…”
Section: In Vivo Cytolytic T Cell Assaymentioning
confidence: 99%
“…The investigators therefore suggested that the loss of transgene production was caused by cellular immunity. 38,[41][42][43] The notion that cellular immunity is directed against the capsid protein may seem counterintuitive, because the vector does not express the capsid gene; instead, the capsid protein present in the recombinant vector at the time of administration seems to persist for several weeks in vivo, marking targeted cells for immunemediated cytotoxic destruction. The scientific quandary ironically derives from the fact that no such reaction seems to occur in any animal model.…”
Section: Cellular Immunity: Man Versus Micementioning
confidence: 99%